Cerebral amyloid angiopathy in Down syndrome and sporadic and autosomal‐dominant Alzheimer's disease. Issue 11 (29th April 2017) - Carmona‐Iragui, María; Balasa, Mircea; Benejam, Bessy; Alcolea, Daniel; Fernández, Susana; Videla, Laura; Sala, Isabel; Sánchez‐Saudinós, María Belén; Morenas‐Rodriguez, Estrella; Ribosa‐Nogué, Roser; Illán‐Gala, Ignacio; Gonzalez‐Ortiz, Sofía; et al.
Abstract: Introduction: We aimed to investigate if cerebral amyloid angiopathy (CAA) is more frequent in genetically determined than in sporadic early‐onset forms of Alzheimer's disease (AD) (early‐onset AD [EOAD]). Methods: Neuroimaging features of CAA, apolipoprotein ( APOE ), and cerebrospinal fluid amyloid β (Aβ) 40 levels were studied in subjects with Down syndrome (DS, n  = 117), autosomal‐dominant AD (ADAD, n  = 29), sporadic EOAD ( n  = 42), and healthy controls ( n  = 68). Results: CAA was present in 31%, 38%, and 12% of cognitively impaired DS, symptomatic ADAD, and sporadic EOAD subjects and in 13% and 4% of cognitively unimpaired DS individuals and healthy controls, respectively. APOE ε4 genotype was borderline significantly associated with CAA in sporadic EOAD ( P  = .06) but not with DS or ADAD. There were no differences in Aβ040 levels between groups or between subjects with and without CAA. Discussion: CAA is more frequently found in genetically determined AD than in sporadic EOAD. Cerebrospinal fluid Aβ40 levels are not a useful biomarker for CAA in AD. Highlights: Cerebral amyloid angiopathy neuroimaging features are more frequently found in genetically determined Alzheimer's disease (AD) than in sporadic early‐onset AD. Cerebrospinal fluid amyloid‐β40 levels are not a useful biomarker for cerebral amyloid angiopathy in AD. The APOE ε4 allele might be associated with cerebral amyloid angiopathy in sporadic early‐onset AD but does not seem to have an effect in genetically determined AD.